Influence of online consumer innovativeness behavior in eletronic products on planned obsolescence process - Neckel, Anderson; Boeing, Ricardo (Revista de Administração da UFSM, 2019)
The objective of this paper is to analyze the influence of online consumer behavior innovativeness on the planned obsolescence process. Through a theoretical analysis of innovativeness constructs, consumer behavior and planned obsolescence process, the following scales and the following model for research development were employed: Domain Specific Innovativeness and New Involvement Profile scales and the Model of Diffusion of Innovations. The research approach uses mixed methods and was performed with two focus groups after a survey was carried out. The sample comprises 448 consumers of electrical and electronic equipment sold on the internet who reside in the Southern region of Brazil. Data processing was based on a multivariate data analysis and results show that innovativeness behavior has a significant positive influence on the planned obsolescence process.